Left ventricular performance and related haemodynamic changes in Prinzmetal's variant angina pectoris. Issue 1 (January 1971) - Guazzi, M.; Polese, A.; Fiorentini, C.; Magrini, F.; Bartorelli, C.
Abstract : Attacks of Prinzmetal's variant form of angina pectoris are spontaneous, recur cyclically, and present unequivocal electrocardiographic alterations: they are ideal for a detailed haemodynamic study. Four patients with this form of angina were investigated. In each of them episodes occurred of electrocardiographic abnormalities either accompanied or unaccompanied by pain. During the same session, the cardiogram, heart rate, arterial pressure, and right atrial pressure were continuously recorded during periods ranging from 5 to 7 hours in each patient. Cardiac output was measured at selected times. Left ventricular ejection time, isovolumic contraction time, mean rate of isovolumic pressure development, and mean systolic ejection rate were also determined. In the 38 recorded anginal episodes, no circulatory change preceded the cardiographic modifications. From the onset of the electrocardiographic abnormalities to the beginning of their reversion, the following circulatory events were observed: (1) obvious reduction of cardiac output; (2) arterial hypotension; (3) lengthening of isovolumic contraction time and mean rate of isovolumic pressure development; (5) reduction of mean systolic ejection rate. It is concluded: (1) that no circulatory factor interfering with work or oxygen consumption of the heart is responsible for eliciting these anginal episodes; (2) that conspicuous left ventricular impairment occurs during the increasing and steady period of the electrocardiographic abnormalities. As the electrocardiogram started reverting to the pre-attack aspect, cardiac performance rapidly improved and, after a `supernormal' phase, returned in about 2 minutes to basal levels. It is possible that this phase is dependent on a temporary sympathetic compensatory mechanism. No significant qualitative differences were detected between the circulatory pattern of various anginal episodes. The difference was mainly quantitative and the magnitude of the haemodynamic changes correlated well with the degree of the electrocardiographic abnormalities. Pain, when present, seemed just a concomitant symptom not significantly interfering with the circulatory changes associated with the episodes of this form of angina pectoris.